1961
DOI: 10.1113/jphysiol.1961.sp006720
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potentials in mammalian cerebral tissues in vitro: dependence on ionic environment

Abstract: Slices of cerebral tissues from guinea-pigs or cats can be maintained in moist oxygen at the surface of salines in a condition which permits the measurement of resting membrane potentials (Li & McIlwain, 1957). This technique gives an opportunity of comparing the effects of substances on polarization and metabolic phenomena in the slices. The present investigation examines the effect of the following cations on the membrane potential: potassium, sodium, calcium, magnesium and ammonium. L-and D-glutamate were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

1966
1966
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(24 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…(21--23). A certain small amount of external sodium was necessary in the establishment of resting membrane potential in mammalian cerebral cortical slices, and when the medium was deprived of sodium, the resting potential was not observed (14), but the external sodium over a certain critical concentration scarcely affected the resting potential (14,21). In the same way, the production of action potential required the existence of external sodium and its concentra tion difference across the membrane, and the changes in the action potential were dependent on the external sodium concentration (21,(23)(24)(25).…”
Section: Besides Itmentioning
confidence: 99%
See 4 more Smart Citations
“…(21--23). A certain small amount of external sodium was necessary in the establishment of resting membrane potential in mammalian cerebral cortical slices, and when the medium was deprived of sodium, the resting potential was not observed (14), but the external sodium over a certain critical concentration scarcely affected the resting potential (14,21). In the same way, the production of action potential required the existence of external sodium and its concentra tion difference across the membrane, and the changes in the action potential were dependent on the external sodium concentration (21,(23)(24)(25).…”
Section: Besides Itmentioning
confidence: 99%
“…was said that after the preparation of separated mammalian cerebral cortical tissue, the tissue reached approximate stability in its Na, K and Cl ions about 15 to 30 minutes after it was incubated by oxygenated glucose-containing medium (12) ; Pappius et al (13) have also reported on the same tendency concerning K ion and stated that such an equi librium state continued for about 60 minutes; the reappearance of the resting membrane potential in cerebral tissue in vitro also required some 20 to 30 minute incubation (14). Thus, it seems that the tissue in vitro requires incubation for a certain interval of time before it reaches astate of equilibrium.…”
Section: Besides Itmentioning
confidence: 99%
See 3 more Smart Citations